SYSTEM SOFTWARE FOR HIGH-PERFORMANCE COMPUTING. - Delaney, John (Communications of the ACM, 2023)
The article highlights the Association for Computing Machinery (ACM) member Robert Ross and his research on communication system software for high-performance computing (HPC) systems.